Kinetic study of thermophilic anaerobic digestion of sugarcane vinasse in a single-stage continuous stirred tank reactor - Bayu, Ardian Indra; Lestary, Rara Ayu; Dewayanto, Nugroho; Mellyanawaty, Melly; Wicaksono, Agni; Alvania Kartika, Roberty Wisnu; Sakka, Deni Frans; Azis, Muhammad Mufti; Budhijanto, Wiratni (Elsevier, 2022)
Vinasse, the liquid waste from the bottom of a bioethanol distillation column, is a potential feedstock for biogas production due to its high organic content. Vinasse is discharged at a high temperature, i.e., 60–80 °C. Therefore, thermophilic anaerobic digestion is more efficient to directly treat the vinasse at a high organic loading rate (OLR). This study investigated the performance of thermophilic anaerobic digestion on sugarcane vinasse inoculated with acclimated digested cow manure (DCM). The experiment was run at varied OLRs (1,2; 1.8 and 2.4 gCOD.L−1.day−1). The process was carried out in a continuous stirred tank reactor (CSTR) with controlled pH (7 ± 0.5) and oxidation-reduction potential/ORP (−500 ± 10 mV). During the 111 days of the experiment, we monitored the volatile fatty acids (VFA), total chemical oxygen demand (tCOD), and soluble chemical oxygen demand (sCOD), as well as methane and biogas production rates, to evaluate the reactor performance. The experimental data were fitted on the Anaerobic Digestion Model 1 (ADM 1) using the AQUASIM® software. The data were categorized in three process stages observed in this study: stabilization, enrichment, and steady-state. The kinetic parameters, i.e., the coefficient of affinity (KS,ac, KS,pro) and the specific growth rate (km,ac and km, pro), were obtained from the data fitting. The good fit of ADM 1 to the data highlighted the flexibility of ADM 1 to represent a dynamic system of a thermophilic anaerobic digestion system with simultaneous changes in both process variables and microbial composition. The data fitting gave consistently low Ks values in the lower OLR of 0.2 gCOD. L−1.day−1 up to the higher OLR of 2.4 gCOD. L−1.day−1. The Ks values, which were less than 1/1000 of the specific growth rate constants (km), indicated that the combined effects of the thermophilic condition and vinasse composition increased the microbial-substrate affinity (showed by KS) more essentially than the microbial growth rate (addressed by km). In addition, inhibitory effects were not observed with all OLR values tested in this study. © 2022 The Authors